Decoding the Structural Dynamics and Conformational Alternations of DNA Secondary Structures by Single-Molecule FRET Microspectroscopy - Bandyopadhyay, Debolina; Mishra, Padmaja P. (Frontiers in Molecular Biosciences, 2021)
In addition to the canonical double helix form, DNA is known to be extrapolated into several other secondary structural patterns involving themselves in inter-and intramolecular-type hydrogen bonding. The secondary structures of nucleic acids go through several stages of multiple, complex, and interconvertible heterogeneous conformations. The journey of DNA through these conformers has significant importance and has been monitored thoroughly to establish qualitative and quantitative information about the transition between the unfolded, folded, misfolded, and partially folded states. During this structural interconversion, there always exists specific populations of intermediates that are short-lived or sometimes even do not accumulate, within a heterogeneous population and are challenging to be characterized by conventional analytic techniques. The single-molecule FRET (sm-FRET) microspectroscopic method has the advantages to overcome these limitations and monitors biological phenomena happening at a measurable high rate and balanced over time stochastically. Thus, tracing the time trajectory of a particular molecule enables direct measurement of the rate constant of each transition step, including the intermediates that are hidden in the ensemble level due to its low concentrations. This review is focused on the advantages of the employment of sm-FRET to access dynamic architecture and structural transition of various secondary structures that DNA adopts, without letting them cross-talk. We have emphasized the studies performed to explore the states of looping and unlooping of several nucleic acid secondary structures, for example, DNA hairpin, Holliday junction, G-quadruplex, and i-motif.